Scaling up kangaroo mother care in South Africa: 'on-site' versus 'off-site' educational facilitation - van Rooyen Elise; Bergh Anne-Marie; Pattinson Robert C (BMC, 2008)
Abstract Background Scaling up the implementation of new health care interventions can be challenging and demand intensive training or retraining of health workers. This paper reports on the results of testing the effectiveness of two different kinds of face-to-face facilitation used in conjunction with a well-designed educational package in the scaling up of kangaroo mother care. Methods Thirty-six hospitals in the Provinces of Gauteng and Mpumalanga in South Africa were targeted to implement kangaroo mother care and participated in the trial. The hospitals were paired with respect to their geographical location and annual number of births. One hospital in each pair was randomly allocated to receive either 'on-site' facilitation (Group A) or 'off-site' facilitation (Group B). Hospitals in Group A received two on-site visits, whereas delegates from hospitals in Group B attended one off-site, 'hands-on' workshop at a training hospital. All hospitals were evaluated during a site visit six to eight months after attending an introductory workshop and were scored by means of an existing progress-monitoring tool with a scoring scale of 0-30. Successful implementation was regarded as demonstrating evidence of practice (score >10) during the site visit. Results There was no significant difference between the scores of Groups A and B (p = 0.633). Fifteen hospitals in Group A and 16 in Group B demonstrated evidence of practice. The median score for Group A was 16.52 (range 00.00-23.79) and that for Group B 14.76 (range 07.50-23.29). Conclusion A previous trial illustrated that the implementation of a new health care intervention could be scaled up by using a carefully designed educational package, combined with face-to-face facilitation by respected resource persons. This study demonstrated that the site of facilitation, either on site or at a centre of excellence, did not influence the ability of a hospital to implement KMC. The choice of outreach strategy should be guided by local circumstances, cost and the availability of skilled facilitators.